PARTICIPATIVE PROCESSES IN THE IMPROVEMENT OF INFORMAL HABITAT IN BOGOTÁ. - FABIO ENRIQUE FORERO SUÁREZ; CAROLINA DORADO LOZANO; ALBA YANETH GALLEGO BETANCUR (Bollettino della Società Geografica Italiana)
The paper is part of a research project carried forward during the past seven years, with the participation of parts of the local community, of students and of professors and more recently with the collaboration of Corporación Sueños Films (and of the «Ojo al Sancocho» film festival promoted by this latter Association); this Association acts as intermediary for the safe access to Localidad 19, Ciudad Bolívar, Bogotá D.C., which is considered unsafe even by the police. Research on the identification of popular habitat has been performed for many years; strategies have been suggested for the implementation of these researches in the development of popular neighborhoods, complemented by the «IAP» process (in English «Research, Action and Participation»), with help from students of architecture and of industrial design and of popular communities. This proposal suggests a strategy for the integrated improvement of habitat incorporating issues of productive residence, of equipment and of public space for informal peripheral neighborhoods, based on the development of a qualitative research performed with participation of students, of experts both from the public and private sectors and of neighborhood communities. This exercise – conceives as an academic contribution to the habitational deficit – has tried to follow the inhabitants of Manitas neighborhood who are involved in the future construction of the Ciudad Bolívar cablecar, so as to give space to future projects and to real «research, action and participation» proposals, incorporating new strategies for social housing based on what is known as Vivienda en Altura Progresiva por Autoconstrucción y Productiva (VAP+A+p, «High-rise, progressive, self-built and productive housing»).